Determination of protease inhibitors, glycinin, and beta‐conglycinin in soybeans and their relationships. Issue 3 (10th February 2022) - Yang, Yu; Chang, Sam K. C.; Zhang, Yan
Abstract : Abstract: In order to search for suitable soybean varieties for different applications, the protein contents of Kunitz trypsin inhibitor (KTI), Bowman–Birk trypsin inhibitor (BBI), glycinin (11S), and β ‐conglycinin (7S) of 93 soybean samples from different sources and harvest years were quantified by sodium dodecyl sulfate polyacrylamide gel electrophoresis. Meanwhile, the protease inhibitory activities against trypsin and chymotrypsin were determined. Results showed that the individual protein contents and trypsin inhibitor activities differed significantly ( p  < 0.05) among soybean samples. KTI contents ranged from 5.25 to 14.60 mg·g −1 ; BBI contents ranged from 1.81 to 5.74 mg·g −1 ; 11S varied from 13.65% to 48.55% and 7S varied from 15.68% to 42.15% of total soluble protein; trypsin and chymotrypsin inhibitory activities were 8.93–20.95 mg TI·g −1 and 4.18 –12.79 mg CI·g −1, respectively. Excellent linear relationships existed between trypsin inhibitor contents and their activities. The regression equations offer a rapid method for estimating the activity of KTI or BBI in raw soybeans. Practical Application: The regression equations established based on a large number of soybean varieties offered a rapid method to estimate the activity of trypsin inhibitors. The data presented here provided useful information for the food industry or breeders to select soybean varieties with different inhibitory activities or protein contents for different food processing applications.